2003
DOI: 10.1152/jn.00513.2001
|View full text |Cite
|
Sign up to set email alerts
|

Neural Processing of Gravito-Inertial Cues in Humans. IV. Influence of Visual Rotational Cues During Roll Optokinetic Stimuli

Abstract: Sensory systems often provide ambiguous information. For example, otolith organs measure gravito-inertial force (GIF), the sum of gravitational force and inertial force due to linear acceleration. However, according to Einstein's equivalence principle, a change in gravitational force due to tilt is indistinguishable from a change in inertial force due to translation. Therefore the central nervous system (CNS) must use other sensory cues to distinguish tilt from translation. For example, the CNS might use dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 55 publications
3
52
2
Order By: Relevance
“…Percepts of roll tilt during sinusoidal variable-radius centrifugation, in particular, appear to support contributions from frequency-segregation. Similar to prior reports in human subjects (Glasauer 1995;Merfeld et al 2005a;Zupan and Merfeld 2005), illusions of roll tilt were greatest at the lowest frequency and became smaller as the frequency of translation increased. While these findings suggest that high and low-pass filters may disambiguate the shifts in GIF produced by head translation Paige and Tomko 1991), the frequency independence of the phase is not consistent with a simple filtering mechanism (Glausauer 1995).…”
Section: Svv Responses During Dynamic Tilt Of the Head Or The Gifsupporting
confidence: 87%
See 2 more Smart Citations
“…Percepts of roll tilt during sinusoidal variable-radius centrifugation, in particular, appear to support contributions from frequency-segregation. Similar to prior reports in human subjects (Glasauer 1995;Merfeld et al 2005a;Zupan and Merfeld 2005), illusions of roll tilt were greatest at the lowest frequency and became smaller as the frequency of translation increased. While these findings suggest that high and low-pass filters may disambiguate the shifts in GIF produced by head translation Paige and Tomko 1991), the frequency independence of the phase is not consistent with a simple filtering mechanism (Glausauer 1995).…”
Section: Svv Responses During Dynamic Tilt Of the Head Or The Gifsupporting
confidence: 87%
“…While we did not measure torsional eye position, prior studies have shown only small torsional deviations of the eyes during roll optokinetic stimulation (Ibbotson et al 2005;Zupan and Merfeld 2003). Therefore it is unlikely that the shift in SVV responses resulted solely from changes in torsional eye position.…”
Section: Svv Responses During Roll Optokinetic Stimulationmentioning
confidence: 84%
See 1 more Smart Citation
“…According to the results obtained by Zupan and Merfeld [16] and by Angelaki and co-workers [17] [which measure linear accelerations of the head (α) and gravity (g)] sense the proprioceptive information from the environment; this is the first step in calculating sensory information from the measurements (α oto , α scc ). In the next step, the measurements are compared with the sensory information predicted by the internal model.…”
Section: The Vestibulo-ocular Reflex Modelmentioning
confidence: 99%
“…The former can be attributed to an illusory traveling perception driven by retinal slip 2) 3) , whereas the presence of a cross-coupling effect on the postural response may indicate that the latter is driven by the velocity storage integrator (VSI) 1) . On the other hand, Ivanenko et al reported that neck vibration induces body sway in the direction of gaze, which they attributed to rotation of the viewer-centered reference frame 4) .…”
Section: Introductionmentioning
confidence: 99%